الحكم الشرعي في الدفع بعدم صلاحية الخاطب: The Shariah Perspective on Defense Against the Unsuitability of a Marriage Proposer - Sadeem Bintu Fahad al-Robei’ (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The importance of this study lies in the impact of substantive defense on the conduct of lawsuits. Substantive defense highlights flaws in the plaintiff's case raised by the defendant, including the defense against an unsuitable marriage proposer in al-'Aḍl cases. Here, the defendant draws the judge's attention to the fact that the plaintiff is seeking marriage with an unfit man, a defense that can only be considered after being examined from legal and jurisprudential perspectives, which is where the importance of this research lies. The study aims to clarify the shariah and legal opinions on the defense against al-'Aḍl claims based on the unfitness of the proposer, addressing issues related to the ruling of al-'Aḍl, its impact on marriage guardianship, criteria for an unfit proposer, and the jurisprudential ruling on prohibiting marriage due to unfitness. The research adopts an inductive, analytical, and comparative approach. The study concludes, among other findings, that al-'Aḍl is prohibited based on consensus (Ijma), marriage guardianship is transferred to the judge if the nearest guardian is disqualified, and the argument to ban marriage based on potential exploitation is not valid. The study recommends further exploration of jurisprudential issues stemming from substantive defenses in all legal proceedings.